Transcriptional adaptations of lipid metabolism in tibialis anterior muscle of endurance-trained athletes - Schmitt, B.; Flück, M.; Decombaz, J.; Kreis, R.; Boesch, C.; Wittwer, M.; Graber, F.; Vogt, M.; Howald, H.; Hoppeler, H. (Physiological Genomics, 2003)
It was hypothesized that transcriptional reprogramming is involved in the structural and functional adaptations of lipid metabolism in human tibialis anterior muscle (TA) from endurance-trained male subjects. RT-PCR experiments demonstrated a significant upregulation of the mRNA level of key enzymes involved in 1) lipolytic mobilization of fatty acids (FA) from intramyocellular lipid (IMCL) stores via hormone-sensitive lipase (LIPE), 2) intramyocellular FA transport via muscle fatty acid binding protein (FABP3), and 3) oxidative phosphorylation (cytochrome c oxidase I, COI), in TA of endurance-trained vs. untrained subjects. In contrast, mRNAs for factors involved in glycolysis (muscle 6-phosphofructokinase, PFKM), intramyocellular storage of FA (diacylglycerol O-acyltransferase 1, DGAT), and ß-oxidation (long-chain acyl-coenzyme A dehydrogenase, ACADL) were invariant between TA of trained and untrained subjects. Correlation analysis identified an association of LIPE with FABP3 and LPL (lipoprotein lipase) mRNA levels and indicated coregulation of the transcript level for LIPE, FABP3, and COI with the level of mRNA encoding peroxisome proliferator-activated receptor- (PPAR-), the master regulator of lipid metabolism. Moreover, a significant correlation existed between LPL mRNA and the absolute rate of IMCL repletion determined by magnetic resonance spectroscopy after exhaustive exercise. Additionally, the LIPE mRNA level correlated with ultrastructurally determined IMCL content and mitochondrial volume density. The present data point to a training-induced, selective increase in mRNA levels of enzymes which are involved in metabolization of intramuscular FA, and these data confirm the well-established phenomenon of enhanced lipid utilization during exercise at moderate intensity in muscles of endurance-trained subjects.